Perspektif Politik Lingkungan dalam Membangun Transportasi Publik Berkelanjutan - Pulina Nityakanti Pramesi; Herdis Herdiansyah; Siti Aminah (Institut Transportasi dan Logistik Trisakti, 2023)
The development of sustainable public transportation is important to overcome environmental problems. In various parts of the world, the development of sustainable public transportation has begun to become a concern. Unfortunately, the development in Depok City has not received serious attention, especially from the government as a policy maker. This article will discuss the low political will of stakeholders in Depok City which will be discussed in the perspective of Environmental Politics. This study uses qualitative descriptive method to describe the political will of actors in Depok City in realizing sustainable development, especially in the field of transportation. Data were collected through in-depth interviews, policy studies, literature studies, and observation which were then analyzed qualitatively using descriptive analysis methods. The results show that the Depok City Government has used the term green transportation in its policies. However, these policies have not been implemented properly, so the problem of green public transportation in Depok City has not been resolved to this day.